Cultural mining landscapes in southern Poland - Szuwarzyński, Marek (Turystyka i krajoznawstwo, 2021)
In southern Poland, in the provinces of Śląskie, Małopolskie, Świętokrzyskie and Podkarpackie, many minerals have been mined for centuries: coal and lignite, metal ores, salt, sulphur and various kinds of stone. Such activity has influenced the natural environment causing permanent changes to surface morphology and aquifers. Together with accompanying changes in the biosphere, they have led to the creation of characteristic mining landscapes. The value of these landscapes has been appreciated in recent years, as evidenced by the inclusion of three historic mining facilities on the UNESCO World Heritage List: Royal Salt Mines in Wieliczka and Bochnia, lead, silver and zinc ore mines in Tarnowskie Góry, and flint mining sites in the vicinity of Krzemionki Opatowskie. In many other cases, they are considered local tourist attractions.